PHYSICO-CHEMICAL AND SOME HEAVY METALS CONCENTRATION ANALYSES ON THREE COMMON SPECIES OF FISH IN TUNGAN KAWO RESERVOIR KONTAGORA, NIGER STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Developing countries like Nigeria are faced with increased in generation of domestic, industrial and agricultural wastes, with a large percentage moving. This study evaluates the physico-chemical and some heavy metals concentration in three common species of fish from Tungan Kawo reservoir Kontagora, Nigeria; using standard methods between (July 2018 â€“ February 2019); at four different sampling stations of human activities on the water. Five heavy metals were evaluated (Lead, Copper, Manganese, Iron and Chromium) in the fish samples. Phosphate (0.4 â€“ 2.5) mg/L, Nitrate (3.2 â€“ 7.5) mg/L, Temperature (27 â€“ 32.4) 0C, Dissolved Oxygen (2.4 â€“ 5.2 mg/L), Conductivity (81 â€“ 125 ÂµS/cm), Biochemical Oxygen Demand (1.9 â€“ 4.4 mg/L), Alkalinity (mg/L) and Total Dissolved Solids (117 â€“ 198) ppm were within the standard for drinking water and survival of fish.  However, the pH (6.3 â€“ 9.8) was above the standard for NIS and WHO drinking water but can support aquatic life. Iron (0.64 Â± 0.072 mg/kg) was the most highly concentrated in Synodontis clarias while lead (0.01 Â± 0.013 mg/kg) was the lowest in Oreochromis niloticus and Coptidon zillii (formerly Tilapia zillii. This current finding indicates that the water is safe for both aquatic life and domestic purpose but not suitable for direct human consumption without being properly treated. However, there is the need for regular monitoring of the heavy metals load in this water body and the aquatic organisms because of the long term effects
Keywords: Kontagora reservoir, physicochemical parameters, Heavy metals, Fish, Human activities